1999
DOI: 10.1093/jn/129.6.1182
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Hepatic Cholesterol and Hepatic Activities of 3-Hydroxy-3-methyl-glutaryl-CoA Reductase and Acyl CoA: Cholesterol Transferase Are Lower in Rats Fed Citrus Peel Extract or a Mixture of Citrus Bioflavonoids

Abstract: The cholesterol-lowering effects of tangerine peel extract and a mixture of two citrus flavonoids were tested. Male rats were fed a 1 g/100 g high-cholesterol diet for 42 d with supplements of either tangerine-peel extract or a mixture of naringin and hesperidin (0.5 g/100 g) to study the effects of plasma and hepatic lipids, hepatic enzyme activities, and the excretion of fecal neutral sterols. Both the tangerine-peel extract and mixture of two flavonoids significantly lowered the levels (mean +/- SE) of plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
182
2
13

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(202 citation statements)
references
References 27 publications
5
182
2
13
Order By: Relevance
“…In mouse models, Citrus flavonoids show marked suppression of atherogenesis through improved metabolic parameters and also through direct impact on the vessel wall. Previous data showed that Citrus peel extract causes lowering of CHOL levels by modulating hepatic HMG-CoA levels 34 . Overall, the scientific evidences obtained with fruits from the Citrus genus provide explanations for the beneficial effects of CD extract in hyperlipidaemic and hyperglycaemic disorders.…”
Section: Discussionmentioning
confidence: 98%
“…In mouse models, Citrus flavonoids show marked suppression of atherogenesis through improved metabolic parameters and also through direct impact on the vessel wall. Previous data showed that Citrus peel extract causes lowering of CHOL levels by modulating hepatic HMG-CoA levels 34 . Overall, the scientific evidences obtained with fruits from the Citrus genus provide explanations for the beneficial effects of CD extract in hyperlipidaemic and hyperglycaemic disorders.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanisms of action are unclear, but hesperetin and=or naringenin have been reported to inhibit estrone sulfatase (Huang et al, 1997) and cytochrome P-450 isoenzymes (Ghosal et al, 1996), to bind to estrogen receptors (Kuiper et al, 1998;Hunter et al, 1999) and to sex hormonebinding globulin (Dechaud et al, 1999), and to act as antioxidants (van Acker et al, 2000;Fuhrman & Aviram, 2001). Furthermore, flavanones have been shown to affect cholesterol metabolism in rats (Bok et al, 1999) and in HepG2 cells (Borradaile et al, 1999), and in a recent study, ingestion of orange juice increased HDL cholesterol levels in hypercholesterolemic human subjects (Kurowska et al, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Hesperidin and naringin (naringenin-7-Oneohesperidoside) have been reported to reduce plasma and hepatic cholesterol, to inhibit HMG-CoA reductase and Acyl CoA:cholesterol O-acyltransferase in rats, and to reduce net apoB secretion in HepG2 cells (Montforte et al, 1995;Bok et al, 1999;Borradaile et al, 1999). These effects may be of benefit for the prevention of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%